Physical fruit growth dynamics in guava (Psidium guajava L.) genotypes - Shubham, J; Amitha, M S; Eldho, V; Manish, S; Arumugam, N; Nayan, D G; Chavlesh, K; Amit, K G; Rakesh, B; Ladup, L; et al. (Plant Science Today, 2026)
Guava (Psidium guajava L.) is a widely cultivated tropical fruit crop valued for its nutritional richness, adaptability and economic importance. This study aimed to investigate the developmental progression of key fruit traits across eleven diverse guava genotypes during the winter season. Fruits were sampled at five growth stages, i.e. 35, 65, 75, 85 days after flowering (DAF) and at physiological maturity (PM) and were evaluated for fruit weight, length, width, seed core diameter and pulp thickness. Significant variation (p ≤ 0.05) was observed among genotypes and across stages for all traits, with the highest values occurring at the PM stage. Genotypes such as Sasni and VNR Bihi recorded the highest values for various fruit physical traits, making them good material for breeding programs focused on fruit size and pulp content. Principal Component Analysis (PCA) revealed that the first three components accounted for 79.46 % of the total variability among genotypes. PC1 (48.97 %) was primarily associated with fruit weight, diameter and seed core diameter at later stages. PC2 (16.15 %) reflected variation in pulp thickness and seed core diameter at mid stages, while PC3 (14.34 %) captured additional differences in fruit length and pulp thickness at maturity. This study provides insights into stage-wise fruit development, enabling future researchers to identify the most appropriate growth stages for recording key fruit traits. These insights will support precise phenotyping and strengthen selection decisions in guava breeding and improvement programs.